0102 Using Augmented Reality In Scientific Posters. (1st November 2014) - Greig, Paul; Higham, Helen
Abstract : Background: The increasing ubiquity of 'smart' devices opens up new possibilities for presenting data. Technology-enhanced learning is a rapidly evolving field, and much progress is made by finding new use for audio-visual technology. Some of these innovations can be difficult to communicate adequately in the traditional paper-based format required for poster presentation. The use of augmented reality (AR) tags in posters offers intriguing new possibilites for incorporating multimedia resources in scientific posters. Innovation: This approach was piloted in our poster 'Perceptual failure: an underrecognised source of error'. The study on which this poster was based tested for perceptual errors (change- and inattentional-blindness) using video based materials. 1 It is known that insight into perceptual errors is very poor, 2 and most people do not recognise that they could be vulnerable to these effects until they are demonstrated to them. The poster created to describe this work was therefore designed to incorporate AR tags using the free 'Aurasma' app, available on Apple iOS (iTunes store), and Android (Google Play). These tags are easy to design and incorporate, and require very little computing knowledge. The technology has an established user base and tags can be made public or private, and can be time-limited. Improvements: Incorporation of AR tags makes for a visually interesting poster that attracts an audience, particularly amongst tech-savvy users. The advantages are that resources can be demonstrated and not simply described. The use of multimedia allows a new freedom to include information that would simply have been impossible previously. Messages: AR tags are simple to set up, and require little prior knowledge. The technology is reasonably mature, and the hardware is already highly prevalent. The opportunities afforded by this new innovation offer a wealth of novel applications in data presentation. References: Greig P, Higham H, Nobre A. Failure to perceive clinical events: an under-recognised source of error. Resuscitation 2014;85:952–6 Levin DT, Momen N, Drivdahl S. Change blindness blindness: the metacognitive error of overestimating change-detection ability. Vis cogn . 2000;7(3):397–412